Experiences of Being Evangelized by the School's Evangelizing Mission: The Case of Employees in a Philippine Catholic University - Pedrosa, Genie U.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
One unique function of a Catholic school is developing a campus-based Christian community and nurturing the Christian life of the members of the academe. The Church stresses its importance in the task of evangelization. Hence, this phenomenological study intended to explore the lived experiences of the permanent employees on the evangelizing mission of a Catholic university. Through a purposive sampling method, the data were gathered from five participants through a semi-structured in-depth interview. The data were analyzed using recursive textual analysis adopting the framework of Lichtman's 3C's. The findings of the study revealed that the evangelizing mission of the university through its religious and outreach activities helped the employees have a more meaningful life, enriched and deepened their faith, and strengthened their relationship with God, the Church, and the members of the institution. They also considered their work as part of the evangelizing mission of the school. In addition, the witnessing of the religious administrators and the visible community life in the university inspired and encouraged them to share in the task of evangelization. Generally, the findings suggest a semblance in the employees' experience and the true identity and mission of Catholic schools highlighted by the Church. This charge is a lifelong challenge for all Catholic institutions to carry out.